Leaf‐level trade‐offs between drought avoidance and desiccation recovery drive elevation stratification in arid oaks. Issue 3 (30th March 2018) - Fallon, Beth; Cavender‐Bares, Jeannine
Abstract: Understanding the extent to which climate limitations drive elevation stratification among species is integral to predicting the impacts of climate change. Zonation patterns of species within mountains have been well documented, and shifts in these patterns have been correlated with recent warming. However, the physiological mechanisms that explain these zonation patterns are not well understood. We used a system of broadly sympatric oak species within semi‐arid mountains to (1) investigate the extent to which species elevation ranges correlate with climate, (2) test for associations of cold and drought resistances with upper and lower elevation limits, and for trade‐offs between resistance mechanisms with elevation, and (3) examine the extent to which species‐wide climatic ranges predict traits that drive local community assembly along an elevation gradient. We found that aridity gradients but not winter minimum temperatures predict oak stratification. Species differed in drought resistance, demonstrating a trade‐off between drought avoidance and drought recovery. At lower elevations, species avoided drought stress during the dry season through leaf abscission; at upper elevations, they maintained transpiration but recovered from daily desiccation via higher leaf water storage capacity, rather than tolerating desiccation via lower turgor loss points. Freezing resistance, measured as stem electrolyte leakage, was not correlated with elevation differences. Taken together, these results indicate that elevation stratification is linked to drought resistance rather than freezing resistance. We also found evidence of niche partitioning among closely related oaks linked to contrasting leaf phenology. The functional, phenological, and physiological traits important for elevation stratification were correlated with species' range‐wide mean annual precipitation and precipitation seasonality, but not aridity. Our findings indicate that drought resistance along a leaf avoidance–recovery trade‐off is integral to species stratification within this semi‐arid montane system. Additionally, the mechanism of stratification acts upon traits and strategies conserved at the species level. Species within this system are likely vulnerable to range retraction under increased drought as a consequence of this phenological avoidance–physiological tolerance trade‐off.